Immunotherapy trial as diagnostic test in evaluating patients with presumed autoimmune gastrointestinal dysmotility - Flanagan, Eoin P. (2014)
BACKGROUND: Chronic gastrointestinal dysmotility greatly impacts the quality of life. Treatment options are limited and generally symptomatic. Neural autoimmunity is an under-recognized etiology. We evaluated immunotherapy as an aid to diagnosing autoimmune gastrointestinal dysmotility (AGID). METHODS: 23 subjects evaluated at the Mayo Clinic for suspected AGID (August 2006-February 2014) fulfilled the following criteria: 1) prominent symptoms of gastrointestinal dysmotility with abnormalities on scintigraphy-manometry; 2) serological evidence or personal/family history of autoimmune disease; 3) treated by immunotherapy on a trial basis, 6-12 weeks (intravenous immune globulin, 16; or methylprednisolone, 5; or both, 2). Response was defined subjectively (symptomatic improvement) and objectively (gastrointestinal scintigraphy/manometry studies). KEY RESULTS: Symptoms at presentation: constipation, 18/23; nausea or vomiting, 18/23; weight loss, 17/23; bloating, 13/23; and early satiety, 4/23. Thirteen patients had personal/family history of autoimmunity. Sixteen had neural autoantibodies and 19 had extra-intestinal autonomic testing abnormalities. Cancer was detected in 3 patients. Pre-immunotherapy scintigraphy revealed slowed transit (19/21 evaluated; gastric, 11; small-bowel, 12; colonic, 11); manometry studies were abnormal in 7/8. Post-immunotherapy, 17 (74%) had improvement (both symptomatic and scintigraphic, 5; symptomatic alone, 8; scintigraphic alone, 4). Nine responders reevaluated had scintigraphic evidence of improvement. The majority of responders who were re-evaluated had improvement in autonomic testing (6 of 7) or manometry (2 of 2). CONCLUSIONS & INFERENCES: This proof of principle study illustrates the importance of considering an autoimmune basis for idiopathic gastrointestinal dysmotility and supports the utility of a diagnostic trial of immunotherapy.